The Estimation of a Hybrid Cost Function for a Railroad Firm - Braeutigam, Ronald R.; Daughety, Andrew F.; Turnquist, Mark A. (The Review of Economics and Statistics, 1982)
Ronald R. Braeutigam, Andrew F. Daughety, Mark A. Turnquist, The Estimation of a Hybrid Cost Function for a Railroad Firm, The Review of Economics and Statistics, Vol. 64, No. 3 (Aug., 1982), pp. 394-404